Co-location of seaweed farming with offshore wind energy: a quick scoping review - Brianna Coffey; Cortni Borgerson; Pankaj Lal; Colette J. Feehan (Frontiers in Marine Science, 2025)
Seaweed farming is increasingly recognized as a sustainable marine resource management opportunity, but it also poses socioeconomic and environmental risks that require careful evaluation. This quick scoping review (QSR) examines the current state of knowledge on upscaling seaweed farming through co-location with offshore wind energy production. A total of 240 published records from 2001 to 2022 were analyzed, including studies on general seaweed farming and its integration with offshore wind energy, both of which have shown a significant increase in annual publication rates over time. Geographically, the majority of studies on general seaweed farming were conducted in Asia, while most research on wind-focused integration was carried out in Europe. Differences in cultivated species were evident, with red seaweeds dominating the general literature and brown seaweeds dominating wind-focused studies. Ecosystem service analysis revealed that provisioning services were disproportionately emphasized, while cultural services were underrepresented in wind-focused studies as compared to the general literature. Environmental constraints were the most frequently cited challenges across both datasets, but their nature differed: general literature highlighted issues such as pests, diseases, and epiphytes that reduce farm yield, while wind-focused studies emphasized risks of farms to local species, habitats, and ecosystems. While environmental knowledge gaps were the most frequently cited overall, legal knowledge gaps were predominant in wind-focused studies. These findings underscore the need for more geographically and taxonomically diverse studies on seaweed-wind multi-use, along with further investigation into cultural services in offshore contexts, strategies for mitigating environmental risks, and the development of frameworks for shared governance to advance sustainable ocean development.